2014
DOI: 10.1136/vr.101580
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility and genetic characterisation of oxytetracycline‐resistant Edwardsiella tarda isolated from diseased eels

Abstract: Edwardsiellosis is one of the most important bacterial diseases in eels. Edwardsiella tarda (E. tarda) isolates (n=94) from diseased eels were screened against the eight most commonly used antimicrobial agents in aquaculture in Taiwan. These isolates were highly susceptible to ampicillin, amoxicillin, florfenicol, oxolinic acid and flumequine. In total, 20 of the 94 (21.3 per cent) isolates tested were resistant to oxytetracycline (OTC). Among the 20 tetracycline-resistant E. tarda isolates, tet(A) was the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 38 publications
(49 reference statements)
0
34
0
Order By: Relevance
“…Numerous researchers have also reported that E. tarda isolates in fish in various countries are highly resistant to ampicillin and amoxicillin (Lee & Wendy, ; Ogbonne, Ukazu, & Egbe, ; Shetty et al, ; Wimalasena et al, ). Previous studies have demonstrated that E. tarda is sensitive to oxytetracycline and sulpha‐trimethoprim (Castro, Toranzo, Barja, Nunez, & Magarinos, ; Shetty et al, ; Stock & Wiedemann, ), while the appearance in red tilapia, olive flounder, red sea bream and eels of E. tarda which is resistant to oxytetracycline and sulpha‐trimethoprim has been frequently reported (Lee & Wendy, ; Lo et al, ; Wimalasena et al, ). These observations suggest that there is a general trend of increasing resistance to oxytetracycline and sulpha‐trimethoprim of E. tarda isolates in aquaculture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous researchers have also reported that E. tarda isolates in fish in various countries are highly resistant to ampicillin and amoxicillin (Lee & Wendy, ; Ogbonne, Ukazu, & Egbe, ; Shetty et al, ; Wimalasena et al, ). Previous studies have demonstrated that E. tarda is sensitive to oxytetracycline and sulpha‐trimethoprim (Castro, Toranzo, Barja, Nunez, & Magarinos, ; Shetty et al, ; Stock & Wiedemann, ), while the appearance in red tilapia, olive flounder, red sea bream and eels of E. tarda which is resistant to oxytetracycline and sulpha‐trimethoprim has been frequently reported (Lee & Wendy, ; Lo et al, ; Wimalasena et al, ). These observations suggest that there is a general trend of increasing resistance to oxytetracycline and sulpha‐trimethoprim of E. tarda isolates in aquaculture.…”
Section: Discussionmentioning
confidence: 99%
“…E. tarda is also a zoonotic pathogen with a broad range of hosts (Xu & Zhang, ). Antibiotics have been the primary measure for controlling and treating bacterial infection in aquaculture (Lo, Lee, Wang, & Kuo, ). However, the overuse and misuse of antibiotics have promoted the emergence of antibiotic‐resistant bacteria, which has significant potential for developing into a crisis in the aquaculture industry, in the environment and in humans (Qiao, Ying, Singer, & Zhu, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extralabel administration of florfenicol (Aquaflor, Merck Animal Health, Madison, NJ, USA) medicated feed was initiated by veterinary feed directive (VFD) in accordance with CPG 615.115 Extralabel Use of Medicated Feeds for Minor Species (FDA, ). Although antibiotic breakpoints are not available for E. piscicida , florfenicol was chosen based on its low MIC and efficacy towards other Edwardsiella species (Lo, Lee, Wang, & Kuo, ; McGinnis, Gaunt, Santucci, Simmons, & Endris, ; Reichley et al, ). The two ponds were fed once daily at a rate of 15 mg of active ingredient per kg of fish body weight per day for 10 days followed by a 42‐day withdrawal period.…”
Section: Antibiotic Minimum Inhibitory Concentrations (Mic) Against Tmentioning
confidence: 99%
“…Free and phagocytized bacterial rods were observed within the lumens of lamellar capillaries (Figure 3d). Mild-to-moderate granulomatous infiltrates, with and without observable bacteria, partially enveloped the olfactory nerves (Figure 3e) E. piscicida, florfenicol was chosen based on its low MIC and efficacy towards other Edwardsiella species (Lo, Lee, Wang, & Kuo, 2014;McGinnis, Gaunt, Santucci, Simmons, & Endris, 2003;Reichley et al, 2018). The two ponds were fed once daily at a rate of 15 mg of active ingredient per kg of fish body weight per day for 10 days followed by a 42-day withdrawal period.…”
mentioning
confidence: 99%